Dampak Aktivitas Penangkapan Terhadap Keanekaragaman Hayati Di Perairan Terumbu Karang - Darwin (CV. SINAR HOWUHOWU, 2025)
Coral reef ecosystems are vital habitats for a wide range of marine species and hold significant ecological and economic value. However, uncontrolled and destructive fishing activities pose a major threat to the sustainability of these ecosystems. This study aims to analyze the impact of fishing activities on biodiversity in three coral reef areas in Indonesia: Raja Ampat, Wakatobi, and the Thousand Islands. A mixed-methods approach was employed, involving underwater surveys, semi-structured interviews, and document analysis. The results indicate that high fishing intensity negatively affects species diversity indices and live coral cover. Areas with effective conservation management exhibited healthier ecosystem conditions compared to those lacking adequate regulations. These findings highlight the importance of enforcement, community involvement, and gear restrictions in preserving coral reef biodiversity. This research contributes to the development of ecosystem-based and participatory strategies for sustainable marine resource management.